A Comparative in Vitro Assessment of Contemporary Biomimetic Re-mineralization Agents on Artificial Enamel Lesions: A Standardized pH-Cycling Model - Abdulbaset Sherif; Ashraf Mujahed (Khalij-Libya Journal of Dental and Medical Research, 2025)
This study aimed to evaluate and compare the remineralizing efficacy of four contemporary biomimetic agents—Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP), Functionalized Tricalcium Phosphate (f-TCP), Nano-Hydroxyapatite (n-HAp), and Nano-Bioactive Glass (n-BAG)—against a standard sodium fluoride (NaF) control and a negative control using a standardized pH-cycling model on primary tooth enamel. One hundred fifty enamel slabs were prepared from non-carious human primary molars. After baseline assessments of surface microhardness (Vickers Hardness Number, VHN) and elemental composition (Ca/P ratio via EDX), artificial caries-like lesions were created. Samples were randomly allocated into six groups (n=25) for a 21-day pH-cycling regimen. Treatment groups received daily applications of their respective agent, while the negative control received deionized water. Post-treatment, microhardness, EDX, and scanning electron microscopy (SEM) were repeated. Demineralization significantly reduced microhardness and Ca/P ratios in all groups (p<0.0001). After pH-cycling, all biomimetic agents significantly outperformed the NaF and negative controls (p<0.05). The negative control showed minimal recovery. NaF improved surface hardness but did not reach baseline levels. The biomimetic agents showed superior and deeper remineralization. n-BAG and n-HAp groups achieved VHN and Ca/P ratios statistically equivalent to sound enamel baseline (p>0.05), indicating near-complete recovery. CPP-ACP was significantly more effective than f-TCP (p<0.05). SEM revealed a dense, homogenous, well-integrated mineral layer for n-HAp and n-BAG, contrasting with the partially occluding deposits of other groups. Contemporary biomimetic remineralization agents, specifically n-BAG and n-HAp, were significantly more effective than traditional sodium fluoride in repairing artificial enamel lesions on primary teeth under in vitro conditions. The efficacy hierarchy was n-BAG ≈ n-HAp > CPP-ACP > f-TCP > NaF.